Students’ Experiences of e-learning: A Virtual Ethnography into Blended Online Learning - Krüger, Simone (Proceedings of the International Conference on Networked Learning, 2006)
This paper discusses results of research-in-progress into students’ experiences of e-learning at Edge Hill, which has derived from the researcher’s virtual ethnographic research and active participant-observation during a blended online module, which was modeled on a social constructivist learning approach. In my ethnographic analyses, two broad themes emerged, namely motivational issues pertinent to e-learning in general, and issues of identity formation in asynchronous discussions. Focusing on both aspects, this paper aims to illuminate e-learning’s potential for enhanced learning among self-motivated learners and those participants who succeeded in building motivation as a result of constructing social identity.